PEMBELAJARAN TARI BEDANA MODEL TEAMS GAMES TOURNAMENTS SMP N 16 BANDAR LAMPUNG - Fani Santi Aziza; Muhammad Fuad; Susi Wendhaningsih (Jurnal Seni dan Pembelajaran, 2016)
The objective of this research was to describe the processes and learning results of bedana dance in SMP N 16 Bandar Lampung. This research used behavioral learning theory. This was a descriptive qualitative research. Data were collected by using observation, interview, documentation, test of practice, and activeness of students. Data sources came from school principal, one teacher and 12 students. Steps in using Teams Games Tournaments model were that the teacher delivered learning objectives, delivered materials with demonstrations, the teacher divided students into groups, the teachers conducted Games Tournaments, the teacher evaluated results of students, and the best performers were awarded. The result showed that the application of Teams Games Tournaments model was not good, the teacher didnt change groups in each meeting and didnt make any variation in the games. Learning results showed that students in the aspect of memorizing sequential movements and simultaneity obtained average grade of 87% with very good criteria.Tujuan penelitian adalah mendeskripsikan proses dan hasil pembelajaran tari bedana di SMP N 16 Bandar Lampung. Teori yang digunakan adalah behavior. Jenis penelitian adalah deskriptif kualitatif. Teknik pengumpulan data yang digunakan adalah panduan observasi, panduan wawancara, panduan dokumentasi, tes praktik dan non-tes. Sumber data dalam penelitian adalah kepala sekolah, guru dan 12 siswa. Langkah-langkah penerapan model Teams Games Tournaments yaitu, guru menyampaikan tujuan pembelajaran, guru menyampaikan materi, guru membagi kelompok, guru mengadakan Games Tournaments, guru mengevaluasi siswa dan kelompok terbaik diberi penghargaan. Hasil pembelajaran ragam gerak tari bedana menggunakan model Teams Games Tournaments belum baik dalam penerapannya, guru tidak mengubah kelompok dalam setiap pertemuan dan tidak melakukan variasi dalam Games, dari aspek penilaian guru menunjukkan bahwa siswa memperoleh rata-rata 87% dengan kriteria baik sekali.Kata kunci: model kooperatif, pembelajaran, tari bedana.